The Financial Challenges of Developing Countries for Climate Change Mitigation and Sustainable Development Under UN Agenda 2030 - Muslim , Hamdiyah Shakir (Journal of Ecohumanism, 2024)
The study seeks to analyze the financial obstacles confronting poor nations in mitigating the effects of climate change and shifting towards sustainable development trajectories, as outlined in the 2030 Agenda. The paper examines Iraq to highlight difficulties and possibilities pertinent to its context, while the analysis and policy implications extend to several other nations in other areas with analogous concerns. The study employs a quantitative analytical methodology using secondary data on sustainable development indicators, emissions, mortality rates, and finance sources for a sample of 18 developing nations from 2010 to 2020, together with projected data for specific economic indicators extending to 2050. The findings indicate that emerging nations, particularly impoverished ones, would encounter the most significant dangers from climate change while not being accountable for its causation. Developing nations are experiencing escalating environmental concerns due to climate change, including floods, droughts, pollution, desertification, and declining water levels. Consequently, these nations must intensify their efforts to address these difficulties and develop measures to safeguard the environment and natural resources. Numerous developing nations depend significantly on the agricultural sector for revenue and employment, confronting emerging difficulties from climate change that result in diminished agricultural output and land degradation, impacting food security and the local economy. Climate change may adversely affect emerging nations' economies, leading to agricultural land degradation and heightened expenses for infrastructure reconstruction.